Principal's Managerial Leadership Strategy in Maintaining the Sustainability of New Student Enrollment at SMAN 1 Cisaga Ciamis - Helmawati, Helmawati; Kuswanda, Wawan; Riyanti, Rini; Rosmaya, Nenden (Journal of English Language and Education, 2025)
The decline in new student enrolment presents a significant challenge to the sustainability of secondary schools, particularly in non-urban areas. This study aims to analyse the principal's managerial leadership strategy in sustaining new student enrolment at SMAN 1 Cisaga, Ciamis Regency. Employing a qualitative approach, data were collected through in-depth interviews, observations, and document analysis involving principals, teachers, and parents as participants. The findings identify three consistently implemented strategies: strategic planning involving community collaboration, adaptive and technology-based school promotion programmes, and ongoing evaluation of strategy effectiveness. The principal plays a central role in shaping a positive school image through the development of extracurricular activities, strengthening community engagement, and optimising digital communication platforms. These strategies have been effective in enhancing the school's attractiveness and increasing public trust in the institution. The study concludes that managerial leadership that is inclusive, participatory, and responsive to social dynamics is essential for maintaining enrolment stability. Further research is recommended to include a broader range of schools and external variables to enhance the generalisability of the findings.